Biokinetic mechnisms of anthocyanins in red fruits produced in the state of Michoacan, Mexico - Quiroz, Jesús; Lizarazo, Cristian; García, Jesús; Torres, Jorge; García, Israel; Hernández, Jose (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Berry fruits are a rich source of phytonutrients, especially phenolic compounds such as flavonoids, which have antioxidant properties. Among these fruits, the most cultivated and consumed are those of the genus Fragaria (Strawberries) and Rubus (Raspberries, blackberries, dewberries), which have been widely studied for their beneficial effects on human and animal health. One of the most important bioactive compounds of these fruits are anthocyanins, which have shown potential benefits for health by their antimicrobial, anti-inflammatory and anticancer activity. Therefore, the study of anthocyanins is of great pharmaceutical and nutraceutical interest. The objective of this research is to analyze the biokinetic mechanisms of anthocyanins in Rubus adenotrichos and Fragaria x ananassa produced in the state of Michoacán, Mexico. For this purpose, research strategies that included the extraction and quantification of anthocyanins, as well as bioinformatic tools to understand their biosynthetic pathway in the mentioned fruits were used. The use of informatic platforms allowed to identify the regulatory genes and enzymes involved in the biosynthesis of anthocyanins in R. adenotrichos and F. x ananassa, finding that most are common, with some specific differences, and that there are only a few exceptions, such as the enzymes catechol-O-methyltransferase (OMT), UDP-glucosyltransferase (UGT) and beta-glucuronidase (GUSB), which only occur in Rubus adenotrichos and not in Fragaria x ananassa.